Micropropagação e produção de monoterpenos e sesquiterpenos em Plectranthus Ornatus Codd - Soares, Helna Célia Passinho (2010)
Several biotechnology techniques have been new tools for the study of medicinal plants, as well as for the production of homogeneous and productive biomass. Accordingly, this study was to observe aspects of morphogenesis and callogenesis of Plectranthus ornatus and evaluate the volatile organic compounds (VOC) profile in micro propagated plants in vitro and in calli. The micropropagation of P. ornatus was conducted from nodal segments in nutritive Murashige and Skoog (MS) medium, where was noted the process adjustment, micropropagation and protocol acclimatization of plants. Studies relating to the induction of callus and morphogenesis were conducted through MS supplemented with auxins and cytokinins. Micro propagated parts and air plants grown in vitro callus were analyzed in relation to the volatile organic compounds content by micro extraction in solid phase attached to Gas Chromatography/High-resolution Mass Spectrometry. The Micropropagation proved a suitable method for volatile organic compounds production in P. ornatus showing a higher VOC content compared to the mother plant. The best results for micropropagation were recorded using MS medium plus BAP, in which the plants had excellent development and a great adaptation for ex vitro conditions. Callus of P. ornatus showed differences in the appearance, consistency, color, and volatile compounds profile depending on the concentrations of regulators added to nutritive media. Moreover, it was noted that there is a direct relationship between the major constituent concentration α-terpinyl acetate and α-thujene, α-pinene, β-pinene, canfene, sabinene e α-limonene, present in essential oil.